Investigation on the competing effects of clay dispersion and matrix plasticisation for polypropylene/clay nanocomposites. Part II: Crystalline structure and thermo-mechanical behaviour - Dong, Yu; Bhattacharyya, D. (Springer, 2012)
In view of the structure–property relationship, the mechanical property enhancement of polypropylene (PP)/clay nanocomposites can also be associated with the alterations of their crystalline structures and behaviour in addition to the general interpretation of intercalation/exfoliation level and uniform dispersion of more rigid clay platelets with higher aspect ratios in the PP matrix. Wide-angle X-ray diffraction (WAXD) was utilised to evaluate the effects of clay content, maleated PP (MAPP) content (MAPP as the compatibiliser) on PP crystalline structures of nanocomposites. Furthermore, the melting and crystallisation behaviour of PP/clay nanocomposites was also investigated by conducting differential scanning calorimetry (DSC). The thermo-mechanical properties were characterised via dynamic mechanical thermal analysis (DMTA). It is observed that enhancement of mechanical properties are mainly affected by the preferred orientation of PP crystals, the growth of α-PP phase and effective nucleating agent role of additional clay while the excessive amount of MAPP becomes detrimental to these crucial aspects, which is also evidently revealed in DMTA measurements.